KEPEMIMPINAN DALAM TEKNOLOGI PEMBELAJARAN MENUJU PENDIDIKAN YANG BERKUALITAS - Muslem; Nazarullah (Lembaga Studi Agama dan Masyarakat Aceh (LSAMA), 2022)
The development of communication and information technology has very significant benefits for the education sector. Various technologies that can be used in the educational process are referred to as learning technologies. These technologies include presentation slides, projection films, electronic equipment, LCD, TV, computer, wifi, teleconferencing, zoom and others. However, the effectiveness of a learning technology is closely related to the leadership style of the principal. What is the Leadership style in utilizing learning technology that can improve the quality of education? In this paper, it is explained that there are various leadership styles of principals in the use of technology such as managerial leadership, transformational leadership, transactional leadership, and teaching leadership styles. In the use of learning technology, various styles of leadership are needed, however, transformative leaders are able to direct all the potential that exists in schools to achieve the maximum organizational goals.